Ø®ØµØ§Ø¦Øµ Ø§Ù„ØªØµÙˆØ± Ø§Ù„ÙÙ„Ø³ÙÙŠ Ù„Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… ÙˆØ§Ù„ÙˆØÙŠ Ø§Ù„Ù†Ø¨ÙˆÙŠ Ø¹Ù†Ø¯ Ù…Ù†Ø¬ÙŠ Ù„Ø³ÙˆØ¯ ÙÙŠ ÙƒØªØ§Ø¨Ù‡ "Ø¥Ø³Ù„Ø§Ù… Ø§Ù„ÙÙ„Ø§Ø³ÙØ©" - Makmun, Muhammad; Budiningsih, Dessy Yanti Srie (DINIKA : Academic Journal of Islamic Studies, 2019)
This study tries to present the characteristics of philosophical knowledge of the Qur'an and Prophetic Revelation according to Munji Laswad in his book Islam wa al-Falasifa". This book presents the appearance or manifestation of the philosophers' unity (their perspective on Islam) in several theological discourses based on the characteristics of philosophical perspectives. The author finds that philosophers according to Munji Laswad have special characteristics in seeing and understanding Islam and some of the main concepts in it specifically related to their perspective on the Qur'an and Prophetic Revelation. Among these characteristics is a knowledge (depiction of something) that must be connected with the burhan(demonstrative proposition) which is a special feature of the schools of Islamic philosophy. Even this type of burhanis a differentiator between philosophy and others, either theology, Sufism or jurisprudence